A medieval dual-sided jet pendant from Poppleton, York. (1st January 2018) - Parker, Adam; Walter, Anna
Abstract: A jet pendant discovered in Poppleton, York, in 2007 is dual-sided and depicts a Crucifixion scene and a Virgin and Child on the two opposing faces. The pendant, now in the Yorkshire Museum, was unstratified and remains unpublished. It is here considered in terms of its material and form in relation to similar examples from both Yorkshire and Britain. A discussion of the imagery on both sides suggests that the Crucifixion scene could depict the Descent from the Cross and connects the object to the strong comparable evidence linking medieval ecclesiastical jet objects to funerary practices.